Iklan Internet, Kualitas Status Jejaring Sosial (Face Book) Sebagai Media Marketing E-Commer B2C (Business To Consumer) Dan Interaksi Penjual & Pembeli Terhadap Keputusan Pembelian - Sjarifuddin Hasan (Jurnal Manajemen, 2014)
Abstract:  Every company engaged in the field of advertising media through  the internet has opportunities and challenges in the move. This study is directed to observe the activities used in advertising through the internet, media quality facebook  as a marketing medium in the e-commerce B2C (business to consumer) and the interaction  between the seller and the buyer (customer) in deciding on the purchase of Batik Keris  in  Jakarta. This issue has subsequently  been formulated  in  accordance with the data collection study variables, namely the advertising data over the internet, facebciok  as its  medium  quality  marketing  B2C  e-commerce,  and  the interaction between the  seller and the buyer  in the purchase decision Batik Keris. This data is compiled riding  100 respondents using a questionnaire and analyzed using regression analysis model. The results of the study showed that the quality of facebook as an intermediary  media marketing  and B2C e-commerce and the interaction  between the seller and the buyer (customer) found positive and significant impact in deciding the purchase of Batik Keris in Jakarta.